The Economic Impact of Lockdowns: A Persistent Inoperability Input-Output Approach - Krista Danielle S. Yu; Kathleen B. Aviso; Joost R. Santos; Raymond R. Tan (Economies, 2020)
The COVID-19 pandemic has forced governments around the world to implement unprecedented lockdowns, mandating businesses to shut down for extended periods of time. Previous studies have modeled the impact of disruptions to the economy at static and dynamic settings. This study develops a model to fulfil the need to account for the sustained disruption resulting from the extended shutdown of business operations. Using a persistent inoperability input-output model (PIIM), we are able to show that (1) sectors that suffer higher levels of inoperability during quarantine period may recover faster depending on their resilience; (2) initially unaffected sectors can suffer inoperability levels higher than directly affected sectors over time; (3) the economic impact on other regions not under lockdown is also significant.